Кореляцiйна функцiя та сприйнятливiсть iзингового магнетика в околi точки фазового переходу - Pylyuk, I. V.; Kozlovskii, M. P. (Publishing house "Academperiodika", 2019)
The application of the method of collective variables to study the behavior of non-universal characteristics of a three-dimensional Ising-like system in the critical region has been illustrated by an example of the correlation function and the susceptibility. An analytic procedure for the calculation of those characteristics has been developed in the quartic-distribution approximation for order parameter fluctuations. The asymptotics of the correlation function at large distances obtained for the critical temperature (T = Tc) is shown to differ qualitatively from that in the T =/ Tc case because of the presence of the critical regime region for all fluctuation modes.